Evaluation of the effect of dose change of Fe3O4 nanoparticles on electrochemical biosensor compatibility using hydrogels as an experimental living organism model - Ozturk, M.; Okutan, M.; Coskun, R.; Colak, B.; Yalcin, O. (ELSEVIER, 2021)
Morphological, structural, optical and dielectric properties, which provide important information about the technological applications of pure and different dose (2.5%, 5.0%, 7.5% and 10.0%) Fe3O4 nanoparticles (NPs) doped hydrogels were analyzed in detail in this study. The complex dielectric parameters of all the samples are related to the electrode/interface polarization (grain boundary), dielectric relaxation and grain effects in accordance with the Maxwell-Wagner theory and Brownian motion in the broadband frequency regions. Experimental plane plots of the complex electrical modulus for all the samples are explained by the Havriliak and Negami relaxation model represented by two relaxation times (alpha and gamma) associated with resistances created by grain boundary (alpha) and grain (gamma). In the high frequency region, complex electrical modulus plane plots of all the samples were compatible with the Cole-Cole relaxation model corresponding to the equivalent electrical circuit (RC) in the Smith Chart diagram. Koop's theory and electron hopping mechanism formed between Fe3+ and Fe2+ ions in the octahedral lattice are effective on the electrical conductivity values of the samples. As the molarity of Fe3O4 NPs increased, the logarithmic conductivity values of all samples, which a function of the angular frequency and defined by the Jonscher Power Law, Nearly Constant Loss and Super Linear Power Law conductivity mechanisms, were generally increased. From the experimental results, it was concluded that the hydrogels with high doses of Fe3O4 NPs can be used as an electrochemical biosensor in bio-systems since it has the high dielectric, capacitance, low impedance and conductivity values. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Fe3O4 nanoparticles; Hydrogels; Maxwell-Wagner theory; Koop's theory; Electrochemical biosensor; Smith chart; DIELECTRIC-PROPERTIES; AQUEOUS-SOLUTIONS; BROWNIAN-MOTION; METHYLENE-BLUE; COMPOSITE; IMPEDANCE; IRON; CONDUCTIVITY; POLARIZATION; DISPERSION; Chemistry; Physics